Zur Datierung der bronzezeitlichen Siedlung Oloris bei Dolnji Lakoš - Dular, Janez (Arheološki vestnik, 2011)
The article discusses the developmental dynamics of the Bronze Age settlement of Oloris near Dolnji Lakoš, about which varied opinions exist. Further analysis of several forms of pottery and decoration and comparison of the material with the radiocarbon dates of similar settlements has shown that the settlement originated in the Middle Bronze Age (MD III = Bd B2/C1), and reached its peak of prosperity in the period of the Late Bronze Age (SD I = Bd C2 and BD D).